Fatigue level during handgrip test: Comparison between young judo athletes and non athletes - Mortatti, A.; Honorato, R. C.; Lara, J. P. R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The training of young judo athletes involves a lot of intermittent maximal and submaximal isometric handgrip actions, mainly while fighting. However, it is still unclear if this process could generate significant outcomes on strength in adolescents. Therefore, the aim of this study was to analyse the level of fatigue in young judo athletes and untrained young people on a handgrip test. Methods: 40 judo athletes [JA] (13.5 years old ±1.13) and 40 untrained young people [UN] 13,5 years old ±1,15) weight, height and maturational status (Mirwald, 2002) were evaluated. The individuals performed, in both hands, a handgrip strength test consisting of 10 all-out repetitions in 10 seconds with 20 seconds of rest between the repetitions. A digital manual dynamometer was used to assess the mean and the peak of handgrip strength of each repetition. The fatigue index ([maximum - minimum] *100/maximum) was used for mean and peak values to determine percentage of loss in strength during the test. The normality of data was assessed by Shapiro-Wilk test, and, after this, all variables were compared between the groups using T student test. The effect size (cohen`s d) for the fatigue index of mean and peak was calculated. A p-value less than 0,05 was adopted as criteria of statistical significance. Results: JA and UN presented no differences in weight, height and maturational status. The mean of training age in JA was 5.42 years. The fatigue index mean values in the dominant hand were JA: 33.2 ± 6.8 % and UN: 38.3 ± 8.7 % (p: 0.004; ES: 0.65) while the values in the non-dominant hand were JA: 35.3 ± 7.61 % and UN: 38.3 ± 8.3 % (p: 0.09; ES: 0.38). For the peak values of strength, the fatigue index was JA: 31.6 ± 7.44 % and UN: 34.8 ± 8.7 (p: 0.08; ES: 0.38) for the dominant hand, and JA: 34.5 ± 8.3 % and UN: 35.1 ± 7.1% (p: 0.76; ES: 0.06) in the non-dominant hand. Discussion: Despite the equality in the decreasing peak values indicate that both groups could have had same capacity to reach similar values in all repetitions, the significant difference in the mean values showed that JA group had a greater capacity to sustain the isometric contractions at a higher level of strength in comparison to the UN, at least in the dominant hand. Dias et al. (2012) reported similar result in judo athletes when compared with sedentary adult men, indicating that the greatest strength endurance can emerge since the beginning of adolescence and persists until adult age, when judo is practiced.